2004
DOI: 10.1016/j.pain.2004.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Spousal congruence on disability, pain, and spouse responses to pain

Abstract: We examined congruence between chronic pain patients and their spouses on their reports of patient pain severity, patient disability, and spouse responses to pain. Patients reported that they were more physically and psychosocially disabled than their spouses reported them to be. However, spouses reported that the patients' pain was more severe than patients reported. Depressive disorders in the patient and gender interacted with patient-spouse ratings. For physical and psychosocial disability, depressed patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 49 publications
(64 reference statements)
7
59
1
Order By: Relevance
“…Much of this research has examined partners' responses to pain communication (Romano, Jensen, Turner, Good, & Hops, 2000;Romano, Turner, Friedman, & Bulcroft, 1991;Romano et al, 1992;Romano et al, 1995). Spouses often make errors when estimating the pain and disability of persons with pain (Cano, Johansen, & Franz, 2005;Cano, Johansen, & Geisser, 2004b;Clipp & George, 1992;Miaskowski, Zimmer, Barrett, Dibble, & Wallhagen, 1997). The assumption in the pain field has been that each spouse shares the same symbol system, which may not always be the case as in a husband who values visual symbols of pain and a wife who primarily uses verbal symbols.…”
Section: Pain Communication 52mentioning
confidence: 99%
“…Much of this research has examined partners' responses to pain communication (Romano, Jensen, Turner, Good, & Hops, 2000;Romano, Turner, Friedman, & Bulcroft, 1991;Romano et al, 1992;Romano et al, 1995). Spouses often make errors when estimating the pain and disability of persons with pain (Cano, Johansen, & Franz, 2005;Cano, Johansen, & Geisser, 2004b;Clipp & George, 1992;Miaskowski, Zimmer, Barrett, Dibble, & Wallhagen, 1997). The assumption in the pain field has been that each spouse shares the same symbol system, which may not always be the case as in a husband who values visual symbols of pain and a wife who primarily uses verbal symbols.…”
Section: Pain Communication 52mentioning
confidence: 99%
“…Empathy might also account for why spouses often underestimate and overestimate pain and disability in ICPs. 13,16,24,66 Issues discussed and avoided during interactions might be just as important. One study showed that although most patients with chronic pain verbally communicated with their families about pain, they found it inappropriate to talk about the pain unless asked.…”
Section: Where Do We Go From Here?mentioning
confidence: 99%
“…Researchers have found that patients perceive fewer spouse solicitous responses or that there are no patient-spouse differences in perceptions of solicitousness (Cano et al, 2004b;Lousberg et al, 1992;Williamson et al, 1997). Further, the literature reports that patients perceive greater punishing respsonses than spouses perceive, or that there are no mean differences in perceptions of punishing responses (Cano et al, 2004b;Williamson et al, 1997).…”
Section: Agreement On Spouse Responses To Painmentioning
confidence: 99%